“Membaca Zaman": Refleksi Pemikiran Jeihan dalam Lukisannya, 1953-2012 - Herliyana Rosalinda; Dhanang Respati Puguh (Jurnal Sejarah Citra Lekha, 2017)
This research examines on the reflection ofJeihan's thoughttraced via his paintingsproduced during 1953 until 2012. It uses historical method with hermeneutical approach. Jeihan’s childhood experienced abnormalities, that made him marginalized in his family and social environment. As the result, his personality became rough and rebellious. It affected his painting style that tend to be harsh and had no character. This bad temper attached him until 1953, when Jeihan studied painting in Himpunan Budaya Surakarta (HBS), and continued his higher education to Institut Teknologi Bandung (ITB). In order to understand painting style, it can be seen from line and color paintings that always progressed. It can be analyzed into four periods which colored by a different artistic style, that are seeking (1952-1965), discovery (1965-1975), maturation (1975-1985), and reaping period (1986-2012).